Raw Materials and Consumables Required for Shielded Metal Arc Welding (SMAW) Training Practice: Development of a Multi-Criteria Framework for Technical and Vocational Education and Training Institutions - Khimmataliyev Dostonazar Omonovich; Khidirov Urol Dobilovich; Eshankulov Ulash Donyorovich (Action Research Journal Indonesia (ARJI), 2026)
The increasing demand for qualified welding specialists in manufacturing, construction, transportation, and energy sectors has intensified the need for effective welding education within Technical and Vocational Education and Training (TVET) systems. Shielded Metal Arc Welding (SMAW) remains one of the most widely taught welding processes because of its versatility, cost-effectiveness, and industrial relevance. However, many TVET institutions continue to face challenges related to the selection, planning, and management of training materials and consumables. Inadequate material selection frequently results in excessive waste, lower training efficiency, reduced weld quality, and increased occupational safety risks. This study develops a multi-criteria framework for selecting raw materials, welding consumables, auxiliary materials, and personal protective equipment for SMAW practical training. A mixed-methods research design was adopted, combining literature analysis, international standards review, expert evaluation, experimental training implementation, and statistical assessment. Three groups of trainees (n = 75) participated in experimental training programs utilizing different material-selection strategies. Training effectiveness was evaluated through weld quality indicators, skill acquisition rates, defect occurrence, material consumption, safety performance, and cost-efficiency metrics. The findings demonstrate that the systematic alignment of training materials with learner competency levels significantly improves educational outcomes. The proposed framework increased skill acquisition rates by 38%, reduced rework requirements by 47%, and improved overall training efficiency by approximately 25%. Furthermore, the integration of advanced personal protective equipment and localized ventilation systems substantially enhanced occupational safety performance. The study contributes a novel pedagogically adapted material-selection model and provides evidence-based recommendations for TVET institutions seeking to modernize welding curricula and optimize resource management.